The anti-fibrotic agent nintedanib protects chondrocytes against tumor necrosis factor-ɑ (TNF-ɑ)-induced extracellular matrix degradation. Issue 3 (1st March 2022) - Wang, Chuankun; Qu, Lizhe
ABSTRACT: Osteoarthritis is an inflammatory disease of the musculoskeletal system characterized by damaged articular cartilage. Nintedanib is an oral triple kinase inhibitor with anti-fibrotic and anti-inflammatory properties. Thus, we hypothesized that nintedanib might exert a protective effect in chondrocytes and it could be meaningful to repurpose the drug for osteoarthritis. In this study, we aimed to investigate the potential effects of nintedanib on TNF-α-induced cellular injury in CHON-001 chondrocytes. The results show that nintedanib ameliorated TNF-α-induced reactive oxygen species (ROS) production and reduced glutathione (GSH) decrease. Nintedanib reduced the production of pro-inflammatory cytokines interleukin-6 (IL-6) and interleukin-1β (IL-1β) in TNF-α-induced CHON-001 chondrocytes. Nintedanib restored TNF-α caused decreased expression levels of Col II and sry-type high-mobility-group box-9 (SOX-9) in CHON-001 chondrocytes. Moreover, nintedanib ameliorated the TNF-α-caused impairment of protein kinase A/cAMP-response element-binding protein (PKA/CREB) signaling pathway as revealed by the decreased PKA RI expression and increased p-CREB in CHON-001 cells. Inhibition of PKA by H89 abolished the effects of nintedanib on SOX-9 and Col II expression. Taken together, nintedanib presented protective effects on TNF-α-induced oxidative stress, inflammation, and ECM damage in CHON-001 chondrocytes. Mechanically, the effect of nintedanib is associated with the PKA/CREB pathway. These data imply that the anti-fibrotic agent nintedanib may have a potential therapeutic application for osteoarthritis. Graphical Abstract: uf0001